2015
DOI: 10.1021/acs.jpcc.5b02130
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Prediction of Phosphorene and Nanoribbons As Fast-Charging Li Ion Battery Anode Materials

Abstract: Ideal Li-ion battery materials should have a low diffusion barrier, which can realize fast charging/discharging. Here, density function theory (DFT) computations were performed to investigate the possibility of phosphorene and its nanoribbons as anode materials for Li-ion battery. Both phosphorene and its nanoribbons are direct band gap semiconductors, and show semiconductor-to-metal transition upon lithiation with significant charge transfer. Importantly, the computed energy barrier of Li diffuses on phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 31 publications
4
77
0
Order By: Relevance
“…111 The diffusion of Li in phosphorene is ultrafast and anisotropic 112 (1.6 × 10 9 times faster along the ZZ direction than along the AM direction, and 260 times faster than in graphite). Energy barriers for the Li diffusions are very low (~0.09 eV) 112,113 suggesting excellent rate capabilities. Due to significant energy barriers difference (Fig.…”
Section: Applications Of Phosphorene Electronic Devices and Sensorsmentioning
confidence: 99%
“…111 The diffusion of Li in phosphorene is ultrafast and anisotropic 112 (1.6 × 10 9 times faster along the ZZ direction than along the AM direction, and 260 times faster than in graphite). Energy barriers for the Li diffusions are very low (~0.09 eV) 112,113 suggesting excellent rate capabilities. Due to significant energy barriers difference (Fig.…”
Section: Applications Of Phosphorene Electronic Devices and Sensorsmentioning
confidence: 99%
“…[128,[240][241][242][243][244][245][246] For Figure 11. The results showed that phosphorene is highly expected to present great opportunities for both high-performance LIBs and SIBs.…”
Section: Phosphorenementioning
confidence: 99%
“…Typical 2D material, such as graphene or carbon based 2D materials 1-9 , boron nitride (BN) 10 , transition metal dichalcogenides (TMDs) [11][12][13][14] , and black phosphorus (BP) [15][16][17][18][19] , are investigated for applications in high-performance electronic devices in field-effect transistors (FETs) 5,14,18 , thin-film solar cell 20,21 , thermoelectric devices 22,23 and lithium-ion batteries 17,24 . Typical 2D material, such as graphene or carbon based 2D materials 1-9 , boron nitride (BN) 10 , transition metal dichalcogenides (TMDs) [11][12][13][14] , and black phosphorus (BP) [15][16][17][18][19] , are investigated for applications in high-performance electronic devices in field-effect transistors (FETs) 5,14,18 , thin-film solar cell 20,21 , thermoelectric devices 22,23 and lithium-ion batteries 17,24 .…”
Section: Introductionmentioning
confidence: 99%